The impact of stigma and self-esteem on quality of life after burn injury—an empirical analysis using structural equation modeling - Liu, Yanbing; Zhu, Xiumei (Frontiers in Psychiatry, 2025)
ObjectiveTo explore the relationships between stigma, self-esteem, and quality of life in burn patients. This study assesses the mediating role of self-esteem between stigma and quality of life using structural equation modeling, providing a theoretical basis for improving patients’ quality of life.MethodsA convenience sampling method was used to select 264 patients in the rehabilitation phase from the burn department of Shaanxi Provincial People’s Hospital between October 2022 and October 2024. The Chinese version of the Social Impact Scale (SIS), Rosenberg Self-Esteem Scale (SES), and Burn Specific Health Scale – Brief (BSHS-B) were used to assess stigma (higher scores indicate stronger stigma), self-esteem (higher scores indicate higher levels of self-esteem), and quality of life (lower scores indicate better quality of life). Pearson correlation analysis was used to explore the correlations among the variables, and structural equation modeling was employed to analyze the mediating role of self-esteem.ResultsThe total scores for stigma (M = 61.21, SD = 11.58), self-esteem (M = 26.28, SD = 5.24), and quality of life (M = 61.26, SD = 10.58) were found, with significant differences across gender, work status, primary source of medical expenses, and burn severity (P<0.05). Pearson correlation analysis showed that stigma was significantly negatively correlated with both self-esteem and quality of life (P<0.01), while self-esteem was significantly positively correlated with quality of life (P<0.01). Structural equation modeling indicated that self-esteem played a partial mediating role between stigma and quality of life (accounting for 28.37% of the total effect), with good model fit.ConclusionStigma, self-esteem, and quality of life are closely related in burn patients, with self-esteem playing a significant mediating role. Reducing stigma and enhancing self-esteem are important strategies for improving patients’ quality of life, providing a basis for psychological interventions.